Comparative study of an open lagoon with high efficient methane free treatment plant and CDM project in palm oil mill effluent - Lim, Li Qeat (2010)
Treatment of POME has always be the famous research topic in Malaysia due to the rapidly grown of palm oil industry as a very important agriculture in Malaysia. Due to the rapidly grown of palm oil industry in Malaysia, a large volume of POME has been produced at the same time. Raw POME is extremely rich in organic content which means it has high biochemical oxygen demand (BOD). Thus it needs to be treated properly to minimized environmental hazard before discharge into water body. Ponding process or a conventional ponding process has been widely use in Malaysia to treat POME. Although it is simple in operation, it generated large amount of sludge and take up large space areas. Besides that, ponding process is also produce methane gas which bring adverse health to human being and significant contribute to the green house gases emission. Anaerobic treatment has been identified as source of methane gas. Thus many studies had been conducted to develop alternatives methods to treat POME which are more efficient in treating POME by reducing the, high BOD content and capture the emitted methane gases while consuming less land area than ponding process. In this study, a comparison of the current technologies of POME treatment system is conducted. A study is carried out at palm oil mill Lepar Hilir to study the methane gas emission and organic content of POME From the study, it found out that high-efficient methane free POME treatment plants are unable to separate oil and particular from POME using micro-bubbles technology which showing a high biochemical oxygen demand at the result. On the other hands, through Clean Development Mechanism, high biochemical oxygen demand could be reduced significantly and successfully in capture methane gas for the use of electricity.